Revolutionizing lignocellulosic biomass: A review of harnessing the power of ionic liquids for sustainable utilization and extraction - Norfarhana, A. S.; Ilyas, R. A.; Ngadi, Norzita; Othman, Mohd Hafiz Dzarfan; Misenan, Muhammad Syukri Mohamad; Norrrahim, Mohd Nor Faiz (ELSEVIER, 2024)
The potential for the transformation of lignocellulosic biomass into valuable commodities is rapidly growing through an environmentally sustainable approach to harness its abundance, cost-effectiveness, biodegradability, and environmentally friendly nature. Ionic liquids (ILs) have received considerable and widespread attention as a promising solution for efficiently dissolving lignocellulosic biomass. The fact that ILs can act as solvents and reagents contributes to their widespread recognition. In particular, ILs are desirable because they are inert, nontoxic, non-flammable, miscible in water, recyclable, thermally and chemically stable, and have low melting points and outstanding ionic conductivity. With these characteristics, ILs can serve as a reliable replacement for traditional biomass conversion methods in various applications. Thus, this comprehensive analysis explores the conversion of lignocellulosic biomass using ILs, focusing on main components such as cellulose, hemicellulose, and lignin. In addition, the effect of multiple parameters on the separation of lignocellulosic biomass using ILs is discussed to emphasize their potential to produce high-value products from this abundant and renewable resource. This work contributes to the advancement of green technologies, offering a promising avenue for the future of biomass conversion and sustainable resource management.
Keywords: Green solvents; Ionic liquids; Fractionation; Lignocellulosic biomass; Cellulose; CELLULOSE DISSOLUTION; CORN STOVER; MICROCRYSTALLINE CELLULOSE; ZOYSIA-JAPONICA; MIXED-SOLVENT; PRETREATMENT; LIGNIN; IMIDAZOLIUM; WOOD; Biochemistry & Molecular Biology; Chemistry; Polymer Science